(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study objective was to determine the effect of E-Contracting on performance of public hospitals in Kakamega County. The study was founded on diffusion of innovation theory and RBV theory. The study applied descriptive survey research design. The study utilized a sample size of 204 which was derived from a sampling frame of 416 using Yamane 1967 formula. Questionnaire was used to collect data. Validity was determined through discussion with the supervisor and department staff and reliability was also determined by pilot study with a focus on internal consistency. This was measured using the Cronbach alpha coefficient. The measures of central tendency and correlational analysis were also used in data analysis. The study was of utmost significance to the policymakers in the health sector, researchers and academicians and the public hospitals in Kakamega and Kenya at large. The findings were presented in tables and figures. The study revealed that manual processes continue to prevail in contract administration, and the platforms are deficient in sophisticated functionalities to facilitate effective negotiation, monitoring, and collaboration. Besides, the study revealed that although the system does not markedly streamline the purchase process, as demonstrated by the restricted capabilities of e-shopping carts and error checking tools, it offers certain advantages in inventory management and procurement oversight.